Determinant of telecommunication performance in Malaysia / Nur Nadiah Atiqah Mohd Zamri - Mohd Zamri, Nur Nadiah Atiqah (Faculty of Business Management, 2017)
The general objective of this study is to identify the determinants of telecommunication performance in Malaysia. The sample of this study is the average data from 12 companies which is listed on the Main Board of Bursa Malaysia covering period of 2010 until 2015. This study chose return on equity (ROE) as dependent variable while current ratio, debt ratio, earning per share, net profit margin and operating profit margin as the independent variables. In determining the liquidity value, this study used current ratio (CR) which from formula of current assets divided with current liabilities. For measuring the leverage, this study used debt ratio that come from total debt divided with total assets while measuring the earning per share, it was measured by using the net income divide by average outstanding common shares. In measuring the net profit margin, it was measured by using the earnings after tax divide by sales and operating profit margin is measured by dividing a company‟s operating income during a given period by its net sales during the same period. The result is expected that current ratio, debt ratio, earnings per share, net profit margin and operating profit margin variables are significant to the performance. Earnings per share, net profit margin and operating profit margin show a positive significant relationship with the performance of company. However, current ratio and debt ratio show a negative insignificant relationship of the company.